2012
DOI: 10.2164/jandrol.111.015545
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the Na,K‐ATPase α4 Isoform Is Regulated During Sperm Capacitation to Support Sperm Motility

Abstract: ABSTRACT:The a4 polypeptide is a testis-specific isoform of the catalytic subunit of the Na,K-ATPase, which is essential for sperm motility and fertility. In the present study, we have investigated the regulation of activity of the a4 isoform and the relevance of this event for sperm capacitation. We have performed this by taking advantage of the selective high affinity of a4 for the inhibitor ouabain. Our results show that ouabain-sensitive hydrolysis of ATP and uptake of 86 Rb, corresponding to the enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
(87 reference statements)
1
33
0
Order By: Relevance
“…Sperm hyperactivation is also accompanied by hyperpolarization of the sperm plasma membrane (Hernandez-Gonzalez et al, 2006;Chavez et al, 2013;Lopez-Gonzalez et al, 2014). In previous reports, we observed that a4 activity helps maintain the membrane potential (Jimenez et al, 2012). Using the fluorescent indicator DiSC3(5), as previously described (Hernandez-Gonzalez et al, 2006), we were able to investigate the effect of human a4 expression on membrane potential in sperm from wild-type and transgenic mice.…”
Section: Molecular Reproduction and Developmentmentioning
confidence: 91%
See 1 more Smart Citation
“…Sperm hyperactivation is also accompanied by hyperpolarization of the sperm plasma membrane (Hernandez-Gonzalez et al, 2006;Chavez et al, 2013;Lopez-Gonzalez et al, 2014). In previous reports, we observed that a4 activity helps maintain the membrane potential (Jimenez et al, 2012). Using the fluorescent indicator DiSC3(5), as previously described (Hernandez-Gonzalez et al, 2006), we were able to investigate the effect of human a4 expression on membrane potential in sperm from wild-type and transgenic mice.…”
Section: Molecular Reproduction and Developmentmentioning
confidence: 91%
“…Na,K‐ATPase α4 exhibits affinities for Na + ,K + , ATP, and the inhibitor ouabain, which is distinct from the other Na,K‐ATPases; The high affinity of α4 for ouabain has been used as a tool to distinguish the function of α4 from the other Na,K‐ATPase α isoforms (Blanco et al, ; Woo et al, ). This distinct pharmacology has linked Na,K‐ATPase α4 activity to sperm motility, particularly contributing to sperm flagellar beat (Woo et al, ; Woo et al, ; Wagoner et al, ; Jimenez et al, ; Jimenez et al, ). Recent studies in which the α4 isoform was either over‐expressed or knocked‐out in genetically modified mice further established a role for α4 in sperm motility, and showed that this isoform is important for male fertility (Jimenez et al, ,).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly it has been demonstrated that as spermatozoa capacitate in the female genital tract, the catalytic activity of alpha4 is up-regulated due to an increased availability of pumps in the membrane (Jimenez et al, 2012), suggesting that alpha4 supports the hyperpolarization and decreased intracellular sodium concentration characteristic of capacitated spermatozoa. An alternative, and not necessarily conflicting, hypothesis is that since pumps in the membrane of spermatozoa experience dramatic changes in e.g., extracellular sodium levels and membrane potential as the cell passes from testis to oviduct, it could be advantageous with a pump that, like alpha4, responds less to environmental alterations (Clausen et al, 2016).…”
Section: Alpha4mentioning
confidence: 99%
“…Binding of ouabain to Na+/K+-ATPase unleash a cascade of interrelated signal transduction pathways that involves inositol (3, 4, 5)-tris-phosphate receptor, Src kinase, tyrosine phosphorylation, epidermal growth factor receptor, Ras and the Ras/Raf/MEK/MAPK signaling pathway [13][14][15]. Following this scheme, ouabain has shown to influence a wide variety of physiological processes, including proliferation [16,17], growth [18], apoptosis [19][20][21] and cell mobility [22] in different tissues and organs. It also has been shown to influence the regulation of salt-sensitive blood pressure [23], salt handling in the kidney [24], vascular tone, Na + homeostasis [25] and embryonic kidney cell´s survival during malnutrition [26].…”
Section: Introductionmentioning
confidence: 99%